Superior hybrid corn variety selection using AHP method - Santoso A.; Nguyen P.T.; Ilayaraja M.; Shankar K.; Abadi S.; Hashim W.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Corn is one of the economic support from the agricultural sector which has recently shown a positive impact with increasing production from year to year, it has increased to 12.49% per year and is predicted to increase. Increasing corn production has had a very positive impact on economy, reduced imports and increased exports greatly helped Indonesia in improving the economy. Therefore the government strongly supports corn farming in Indonesia so that the government and farmers are aggressively looking for superior seeds for planting, with a faster harvest period and resistance to pests, a decision support system is made to select superior corn varieties with AHP method (analytical hierarchy process). In order to facilitate farmers in selecting superior and profitable types of corn. With this decision support system, it is expected that it can help in selecting the right and accurate corn varieties according to the farmer expectation. BEIESP.